The Private Sector’s Comparative Advantage - Sawyer, Tom (Maine Policy Review, 1993)
At the "Rethinking State Government" conference held at the University of Maine in January 1993, a panel explored the issue of privatization, of using private enterprise to provide public sector services. Tom Sawyer provides his perspective as a private environmental services contractor.